Socioeconomic status and environmental noise exposure in Montreal, Canada - Dale, Laura M (BMC Public Health, 2015)
BACKGROUND: This study’s objective was to determine whether socioeconomically deprived populations are exposed to greater levels of environmental noise. METHODS: Indicators of socioeconomic status were correlated with LAeq24h noise levels estimated with a land-use regression model at a small geographic scale. RESULTS: We found that noise exposure was associated with all socioeconomic indicators, with the strongest correlations found for median household income, proportion of people who spend over 30% of their income on housing, proportion of people below the low income boundary and with a social deprivation index combining several socio-economic variables. CONCLUSION: Our results were inconsistent with a number of studies performed elsewhere, indicating that locally conducted studies are imperative to assessing whether this double burden of noise exposure and low socioeconomic status exists in other contexts. The primary implication of our study is that noise exposure represents an environmental injustice in Montreal, which is an issue that merits both investigation and concern. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-1571-2) contains supplementary material, which is available to authorized users.